Applying Gemini to enhance EFL learning: A review of advantages and challenges - Miftakul Rokhman Purnama; Made Hery Santosa; Ni Nyoman Padmadewi (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2025)
A growing implementation of AI (Artificial Intelligence) is regarded as an educational evolution which brings significant change into English as Foreign Language (EFL) classrooms. Google Gemini is one of generative AI tools commonly used by EFL students in which it is assumed as a double-edged sword that can either be detrimental or beneficial for students’ English proficiency. The current study was conducted to explore the advantages and challenges in integrating Gemini to enhance EFL learning. A Systematic Literature Review was used as a research design particularly by adapting PRISMA framework consisting of four stages; identification, screening, eligibility, and inclusion. There were 42 articles used as sources in which there were only 27 articles selected as the main data. Those articles were published in the reputable journals indexed in SCOPUS, WOS, SINTA, Garuda, and Crossref. The findings revealed that there were six advantages and four challenges in integrating Gemini into EFL classrooms. The advantages were increasing learning motivation, increasing learning interest, making learning efficient, directing self-learning, enhancing writing and speaking skills, and boosting creativity, meanwhile the challenges were a lack of technological resources, technical problems, ethical problems, and deterioration of critical thinking skills. These findings implicate the implementation of generative AI tools in enhancing EFL learning in which the advantages support the integration of Gemini and the challenges can be used as a consideration in optimizing its usage.